Perbandingan Fiqih Dalam Konsep Murabahah: Eksistensi Dan Implementasinya Di Era Kontemporer - Alfie Akhmad Sa'dan Hariri; Fauzan Januri; Ayi Yunus Rusyana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Murabahah has become the most dominant financing instrument in modern Islamic financial institutions. However, in its contemporary development, the implementation of this contract often faces challenges in the form of a shift in essence from the principle of real sale and purchase to merely a monetary financing instrument. The urgency of this article lies in the importance of re-examining the theological and legal roots of the murabahah concept to ensure that the modernization of financial practices does not sacrifice fundamental sharia principles (maqasid asy-syariah). Through a comparison of fiqh views across schools of thought, this article aims to explore the flexibility of Islamic law while critiquing the distortion of contemporary murabahah implementation so that it remains within the corridor of genuine justice and partnership. This research uses qualitative research with a focus on library research. The data sources used are entirely from secondary data, including classical fiqh literature from various schools of thought, fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), positive legal regulations in Indonesia, and relevant scientific journal articles. The analytical method applied is descriptive-analysis combined with critical analysis to dissect the dynamics of legal texts and market realities. The approach used is juridical-normative, which functions to examine the alignment between formal regulations and empirical practices against authoritative fiqh norms. This article discusses three main problem formulations by highlighting the novelty aspect. First, this research compares differences in interpretation between schools of thought regarding the conditions and pillars of murabahah, then highlights the relevance of these differences to the need for legal flexibility in the modern era. Second, a deep gap was found between the idealism of fiqh that prioritizes justice and partnership and the reality of modern financial institutions that tend to be profit-oriented. Third, this article presents a comprehensive integrative analysis by examining the extent to which Indonesian positive law and DSN-MUI fatwas can act as a bridge that maintains sharia compliance amidst the tug-of-war between classical theory and the demands of the contemporary financial industry.